CD8+ T cells induced by adenovirus-vectored vaccine are capable of preventing establishment of latent murine γ-herpesvirus 68 infection. Issue 22 (16th May 2019) - Boilesen, Ditte R.; Ragonnaud, Emeline; Laursen, Henriette; Andersson, Anne-Marie C.; Tolver, Anders; Spiess, Katja; Holst, Peter J.
Abstract: CD8+ T cells are known to control infections, but their role in preventing latent infection from establishing has not been thoroughly investigated. We hypothesized that a potent CD8+ T cell response patrolling the mucosal viral entry points could kill the first infected cells and thereby abrogate the infection before latency is established. To investigate this, replication deficient adenovirus serotype 5 vectors encoding murine γ-herpesvirus-68 CD8+ T cell epitopes linked to the T cell adjuvant Invariant chain, were developed. We show that intranasal vaccination of mice reduces the risk of establishment of latent infection from multiple intranasal ID50 challenges with murine γ-herpesvirus-68 by 81% per exposure at 14 days post vaccination. Protection waned over time, but immune responses were extended by heterologous prime-boost vaccination applied simultaneously intramuscularly and intranasally, and animals vaccinated 66 days prior to challenge showed a strong trend of long-term protection. Our data provides evidence that CD8+ T cells are able to protect against establishment of latent infection. Although the protective efficacy is difficult to maintain over time, this proof-of-concept study suggests a role for a CD8+ T cell arm in future vaccine strategies against latent human viral infections caused by pathogens such as HIV and multiple herpes virus.